PEMANFAATAN MOODLE DALAM IMPLEMENTASI E-LEARNING DI SEKOLAH KEJURUAN (Studi kasus : SMK Bina Jaya Palembang) - Iin Seprina; Evi Yulianingsih (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2021)
SMK Bina Jaya is one of the secondary vocational education as a continuation of SMP/MTS where the learning process is still through face-to-face in class. The learning process carried out in the classroom is very limited in time because, usually the teacher gives instructions to all students about the material to be studied at that time which makes students have limited time. The existence of Information and Communication Technology today will make it easier to get a lesson because, there are facilities that can be accessed through internet media. Where, the process can be done anywhere and anytime, one of the Information and Communication Technology media that can be applied in learning is E-Learning. E-Learning is a medium of learning that is carried out over long distances and must use an internet connection to run it. This study aims to implement an online e-learning system using Moodle software which is open source and free. Moodle learning e-learning is a web-based application that provides online learning services. The research method used is qualitative data (data about student and teacher activities) and quantitative data (data about student learning outcomes at the end of each cycle). Data collection techniques using observation, interviews and documentation, as well as using the development method of Extreme Programming. The results achieved from this research is the interaction between teachers and students in the learning process. In addition, e-learning also functions as a discussion forum between teachers and students, and can be used as an online quiz, so that all activities in the learning process become more effective. More about this source textSource text required for additional translation informationSend feedback Side panels